Enhancement of H2 Sensing via Silica Medium Embedded with Nano Platinum as Gas Sensor - Ghorbani, H.; Binaian, E.; Tayebi, H.; Shokoohirad, A.; Gilaki, M. (Asian Journal of Chemistry, 2012)
A new permeable silicon sensor with nano structures of platinum as hydrogen sensing layer is accessible in this study. This sensor works at room temperature. p-Type silica substrate is prone to permeable silica etching. The substrate is coated with a thin layer of platinum and annealed at 800 ºC. This results in a quantity of platinum getting oxidized on permeable silica and slender platinum oxide layer appearances on the exterior of the substrate. The sensor was tested in the range of 0-1.5 % H2. The sensor responded in real time. Dissimilar conformist thin film-based resistive hydrogen sensors this sensor showed an opposite association along with increased hydrogen concentration versus resistance.